Analisis Pembelajaran Kesetaraan Paket C Sebagai Upaya Peningkatan Partisipasi Belajar Bagi Siswa Outreach (Putus Sekolah) di PKBM Budi Utama Surabaya - 'Aisyah, Siti; Nugroho, Rivo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
Outreach students are school dropouts who receive free access to equivalent education. The purpose of this study is to analyze the process of learning Package C equivalence in efforts to increase learning participation for outreach students. This research is descriptive with a qualitative approach. Data collection techniques include in-depth interviews, participant observation, and documentation. The results of this study indicate that the implementation of Package C equivalence learning for outreach students has been carried out according to the schedule and learning regulations. The implementation of learning is supported by several aspects, such as educators appropriate to the subjects taught, the use of appropriate curriculum, learning strategies through andragogy approaches, and the use of three learning evaluations. However, aspects such as the recognition of the characteristics of outreach students by tutors and the lack of supportive learning media are less supportive. Furthermore, regarding the participation of outreach students, attendance cannot be predicted whether attending face-to-face or online learning, lack of response, and failure to complete assignments.